Simbologia, palimpsestos e intertextualidade no filme coração satânico, de Alan Parker - Kulsar, Paulo Andre Machado (Universidade Federal do Tocantins, 2020)
The present work deals with a detailed analysis of the movie Angel Heart (1987), directed and scripted by the Britishman Alan Parker. The movie was adapted from Willian Hjortsberg's novel Falling Angel (1978), based essentially on three objectives, namely: firstly, an analysis of the symbolic aspects in the film based on the imagery theory proposed by Gilbert Durand, who in his work The Anthropological Structures of the Imaginary (1999) divides image into Day and Night Regimes, and, from this division, he understands how archetypes are signified in various cultures, once in the film we analyzed one finds a great amount of symbols, with predominance of religious ones; secondly there is the analysis of the film as second-hand literature, in Genette's terms, who in his Palimpsests: Literature in the Second Degree (Stages) (1982) treats literary works as palimpsests of earlier works, which in this case leads us to a comparison between Angel Heart and Sophocles' tragedy Oedipus Rex, based on the conception of tragedy presented in Vernant and Vidal-Naquet's Myth and Tragedy in Ancient Greece (1977); and thirdly, the film in question is analyzed based on the thought of St. Augustine of Hippo and his conceptions of free will, evil and divine foreknowledge, present in his works Confessions, City of God and Free Will.